Aspek Hukum Perlindungan Konsumen Terhadap Produk Masker Medis di PT. Surya Tara Jaya - Chen, Andre; Diary Steward Surbakti, Anton (Universitas Ekasakti, 2024)
When talking about the need for masks, this increasing demand is unexpectedly exploited by irresponsible individuals. They carry out hoarding of medical masks and health equipment that are urgently needed by the community and medical teams in dealing with the pandemic. The purpose of this hoarding is to gain profit and enrich themselves by selling medical masks, hand sanitizers, alcohol, and other equipment at above average prices. This research is a normative research. The data collection tools used in this study are in the form of document studies and literature searches. Data obtained from library materials are then analyzed by document studies and using qualitative analysis. Based on the results of the study of legal protection regulations for consumers regulated in Law Number 8 of 1999 regarding medical mask products, it explains that consumer rights include the right to comfort, security, and safety in consuming goods and/or services in accordance with the exchange rate and conditions and guarantees promised, the right to be treated or served properly and honestly and without discrimination. The company's procedure for resolving consumer disputes related to medical mask products at PT. Surya Tara Jaya is an effort to resolve the disputes that can be carried out by PT. Surya Tara Jaya, which suffers losses due to the use of defective health masks, the company takes 2 (two) methods, namely through non-litigation and litigation. Dispute resolution through non-litigation is the initial way to resolve disputes between producers and consumers, while litigation resolution can be carried out if the dispute cannot be resolved through any means or cannot be done through non-litigation dispute resolution. There are several obstacles that companies may face in resolving consumer disputes related to medical mask products. Some of these obstacles involve various factors, including law, communication, and external factors. Here are some of the obstacles that may be faced: regulatory complexity, legal costs, lack of information or poor communication, legal uncertainty, reputational risk, resource constraints, group demands, inconsistent understanding.